Oral and perioral soft tissue lesions and oral functions in patients with dystrophic epidermolysis bullosa - Čolović, Aleksandra; Jovičić, Olivera; Mandinić, Zoran; Mandić, Jelena; Juloski, Jelena (Vojnosanitetski pregled, 2022)
Background/Aim. Dystrophic epidermolysis bullosa (DEB) is characterized by distinct systemic and skin changes, as well as numerous oral manifestations. The aim of the study was to examine oral and perioral soft tissues and oral functions in DEB patients by monitoring changes over a period of one year. Methods. Twenty-four patients (1 month to 36 years old) were clinically examined initially (T0), after 6 months (T6), and after 12 months (T12). Appearance and localization of perioral and oral bullae and scars, maximum mouth opening, reduced vestibule depth, absence of lingual papillae and palatal rugae, and restricted tongue movement due to scarring were monitored. The values of maximum mouth opening at the initial examination were compared to those measured in the healthy control group of the same age. The age of patients and differences between the dominant and recessive subtypes of DEB were analyzed. Results. The average maximum mouth opening was significantly lower in DEB patients compared to healthy individuals. Oral and perioral bullae and scars, microstomia, and reduced vestibule depth were very common, with no statistically significant difference among T0, T6, and T12. The prevalence of restricted tongue movement due to scarring and the absence of lingual papillae and palatal rugae increased significantly over one year. Patients with microstomia, vestibule depth, and restricted tongue movement due to scarring were significantly older than patients without these characteristics. Lingual papillae and palatal rugae were more frequently absent in recessive than dominant DEB. Conclusion. DEB causes significant changes in oral and perioral soft tissues and oral functions impairment.